Stellar Archeology: What White Dwarf Stars Tell Us About the History of the Galaxy - Terry D. Oswalt (Journal of Astronomy and Space Sciences, 2012)
White dwarf stars have played important roles in rather diverse areas of astrophysics. This paper outlines how these stellar remnants, especially those in widely separated “fragile” binaries, have provided unique leverage on difficult astrophysical problems such as the ages of stars, the structure and evolution of the Galaxy, the nature of dark matter and even the discovery of dark energy.